2016
DOI: 10.3233/jad-150606
|View full text |Cite
|
Sign up to set email alerts
|

Lewy Bodies, Vascular Risk Factors, and Subcortical Arteriosclerotic Leukoencephalopathy, but not Alzheimer Pathology, are Associated with Development of Psychosis in Alzheimer’s Disease

Abstract: Background The neuropathological correlates of psychosis in Alzheimer’s disease (AD) is unclear, with some studies reporting a correlation between psychosis and increased AD pathology while others have found no association. Objective To determine the demographic, clinical, and neuropathological features associated with psychotic symptoms in clinically attributed and neuropathologically proven AD. Method We separately reviewed two overlapping groups of clinically diagnosed (cAD) AD patients with neuropathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 49 publications
5
37
2
Order By: Relevance
“…Patients clinically misdiagnosed with a certain type of dementia may be an important subgroup inflicting errors in trials and mixed AD with vascular dementia are often misdiagnosed as pure LDB 1. Our findings of vascular pathology and severe psychosis introduce a possible understanding of this subgroup and may improve diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Patients clinically misdiagnosed with a certain type of dementia may be an important subgroup inflicting errors in trials and mixed AD with vascular dementia are often misdiagnosed as pure LDB 1. Our findings of vascular pathology and severe psychosis introduce a possible understanding of this subgroup and may improve diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 73%
“…Subcortical arteriosclerotic leukoencephalopathy (SVD-related pathology) and vascular risk factors, but not specific vascular pathologies, were found associated with psychosis ever present 1. Vascular changes on MRI have also been associated with late onset schizophrenia, and there is an overlap between late onset schizophrenia and early psychotic symptoms in dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, most studies relied on a clinical diagnosis of AD, which is more prone to error, rather than the gold standard neuropathological diagnosis of AD. In our previous study, we found that using a clinical diagnosis can result in false associations due to the high rates of misdiagnosis [36, 37]. …”
Section: Introductionmentioning
confidence: 99%
“…A study has demonstrated that AD patients tend to develop visual hallucinations significantly later than patients with Dementia with Lewy bodies [28]. Thus, visual hallucinations may characterize the advanced stages of AD and the co-occurrence of vascular pathology rather than AD pathology [29, 30]. …”
Section: Introductionmentioning
confidence: 99%